Development of new restorer lines for CMS ogura system with the use of resynthesized oilseed rape (Brassica napus L.) - Szała, Laurencja (Breed Sci, 2016)
Resynthesized (RS) oilseed rape (Brassica napus L.) is potentially of great interest for hybrid breeding. However, a major problem with the direct use of RS B. napus is the quality of seed oil (high level of erucic acid) and seed meal (high glucosinolate content), which does not comply with double-low quality oilseed rape. Thus, additional developments are needed before RS B. napus can be introduced into breeding practice. In this study, RS oilseed rape was obtained through crosses between B. rapa ssp. chinensis var. chinensis and B. oleracea ssp. acephala var. sabellica. RS plant was then crossed with double-low (00) winter oilseed rape lines containing the Rfo gene for Ogura cytoplasmic male sterility (CMS ogu) system. Populations of doubled haploids (DH) were developed from these F(1) hybrids using the microspore in vitro culture method. The seeds of semi-RS DH lines were analyzed for erucic acid and glucosinolate content. Among the populations of semi-RS DHs four 00-quality lines with the Rfo gene were selected. Using 344 AFLP markers to estimate genetic relatedness, we showed that the RS lines and semi-RS lines formed clusters that were clearly distinct from 96 winter oilseed rape parental lines of F(1) hybrids.